What Motivates Contributors vs. Lurkers? An Investigation of Online Feedback Forums - Phang, Chee Wei; Kankanhalli, Atreyi; Tan, Bernard C. Y. (Information Systems Research, 2015)
Organizations are setting up online forums to obtain inputs and feedback from key stakeholders, such as employees, customers, and citizens. Examples of such virtual spaces are online policy deliberation forums (OPDFs) initiated by government organizations to garner citizens’ views on policy issues. Incorporating the inputs from these forums can result in more inclusive policies for societal benefit. Yet, as with other such forums, a common issue facing OPDFs is the sustainability of participation. When examining this issue, previous research has mostly explored the participation antecedents of existing contributors. However, engaging lurkers is also important, because these forums need to compensate for contributor attrition and become more effective with greater reach. Thus motivated, this study develops a model to explain the antecedents of both contributors’ and lurkers’ participation deriving from public participation and information technology-enabled public goods theories. It hypothesizes differences in the antecedents for contributors versus lurkers based primarily on construal level theory. The model was empirically validated through a survey of contributors and lurkers in a nationwide OPDF. The results reveal significant differences in the participation antecedents of the two groups as hypothesized. Specifically, contributors are influenced by political career benefit and political efficacy motives, whereas lurkers’ future participation intention is driven by collective benefits, possession of civic skills, and mobilization. Furthermore, perceived connectivity of the OPDF directly influences participation intention for contributors and indirectly impacts participation intention for both groups via perceived communality. Perceived communality, on the other hand, influences collective and persuasion benefits for both contributors and lurkers. These findings are useful for understanding and promoting participation through differential strategies for contributors and lurkers in OPDFs in particular, and by extension, other feedback or online forums.